Essays on Bank Lending, Output Growth and Implications for Economic Policy - Michail, Nektarios A. (Department of Commerce, Finance and Shipping, Faculty of Management and Economics, 2016)
The relationship between bank lending and output growth, the subsequent policy implications and the effects of policy on this relationship have been in and out of vogue many times in the academic literature. Even though the recent financial crisis has once again turned our attention to the examination of this connection, studies concerning the effects of bank lending on the overall economy and the policy implications these entail have been few since its onset. This dissertation contributes to the literature by providing three interrelated, mainly empirical, chapters which study different aspects of the relationship between bank lending and output growth, as well as the macroeconomic policies associated with them. The first chapter examines the effect of an increase in total lending in the economy of three euro area countries (Germany, Italy, Spain) by employing a factor-augemented VAR (FAVAR) specification. The benefit of this approach, as evidenced in the literature, is that the inclusion of the factors generates more precise estimates as they incorporate the whole economy into the specification. The contribution is twofold: first, I find that while the average effect of bank lending on output is relatively small, it is always positive with responses varying across countries; second, increases in bank lending, also increase total deposits in the economy, in all sample countries, providing the first macroeconomic evidence for the credit creation theory, i.e. that bank lending creates deposits. In addition, the results suggest that large changes in deposits unrelated to changes in lending can potentially signal distress, a channel policymakers can focus on as a leading indicator. In the second chapter, I examine the effects of private bank lending in the economy using both theory and empirical evidence supplementing the evidence presented in the first chapter. Through a two-period model, I find that even when changes in lending are due to monetary viii easing, a positive relationship between finance and growth exists, while this relationship exhibits diminishing returns after a certain threshold. Furthermore, the theoretical conclusions are tested by employing a smooth transition conditional correlation (STCC) model. The empirical evidence also suggests that the finance-growth relationship is always positive and exhibits diminishing returns after country-specific thresholds. Overall, the results suggest that, other things being constant, private lending promotes GDP growth, at any debt-to-GDP ratio. As such, macro-prudential policies should not emphasise on the level of lending, but how the allocation of these loans affects the workings of the economy. The third chapter focuses on policy issues. The first two chapters establish that the relationship between bank lending and output growth is positive, and more so that there are no thresholds after which it becomes negative, the third chapter asks whether monetary policy has a persistent effect on bank lending behaviour. To answer this question I employ macroeconomic data for 10 euro area (EA) countries and, through the shock persistence methodology developed by Lee et al. (1993), I examine whether monetary policy has persistent effects on bank lending behavior, both directly through the credit channel and indirectly through the risk-taking and liquidity channels. The findings suggest that policy actions aimed at affecting credit risk and bank lending do not have any persistent effects if only the interest rate is employed. Consequently, macro-prudential policy should focus on other factors which affect lending decisions, most notably the liquidity channel as an important determinant of the level of lending.
Keywords: Bank lending; Output growth; Economic policy; Monetary policy; Macro-prudential; STCC; Factor-Augmented VAR; Persistence